Furry Friends : Sophie's Squeaky Surprise - Webb, Holly; Elsom, Clare (London : Scholastic Children's Books, 2016)
A heart-warming and humorous animal series by Holly Webb, with gorgeous illustrations throughout. Sophie isn't happy about moving to a strange new country and starting at a new school. But then she meets Josephine - a macaroon-eating, tutu-wearing guinea pig, who lives with her furry friends in the centre of Paris. Josephine soon shows Sophie that living in a new place is exciting and being friends with a guinea pig is the best adventure of all.
3-6.
Keywords: Friendship -- Fiction; Moving -- Fiction